Inhibition of heme oxygenase in the central nervous system potentiates endotoxin-induced vasopressin release in the rat. - Mancuso, C; Ragazzoni, E; Tringali, G; Liberale, I; Preziosi, P; Grossman, A; Navarra, P (1999)
Previous in vitro studies have shown that increases in endogenous carbon monoxide (CO) generation via activation of the enzyme heme oxygenase (HO) within the rat hypothalamus are associated with the reduced release of the neuropeptides, vasopressin (AVP) and oxytocin, while evidence concerning corticotrophin-releasing hormone (CRH) is controversial. The present study investigated whether there is also a functional relationship between the HO-CO pathway and AVP and corticosterone (Cort) in vivo. Male Wistar rats were challenged with bacterial lipopolysaccharide (LPS) at doses producing significant activation of the hypothalamo-pituitary-adrenal (HPA) axis. LPS was given alone or after pretreatment with the HO inhibitor Sn-protoporphyrin-9 (SnPP9). The latter was injected either intraperitoneally (i.p.) or by intracerebroventricular (i.c.v.) route. SnPP9 given i.p. failed to modify either basal or LPS-stimulated levels of AVP and Cort. On the contrary, i.c.v. SnPP9 strongly potentiated LPS-induced AVP release and significantly enhanced basal serum Cort levels, although it failed to potentiate stimulation by LPS. The LPS + i.c.v. SnPP9 also significantly reduced the hypothalamic stores of AVP compared to controls, correlating with increased circulating levels of AVP. Taken collectively, these data are in concordance with previous in vitro observations showing that the HO-CO pathway acts centrally to attenuate endotoxin-stimulated AVP release, while having less effects on the pituitary-adrenal axis.